A didática em sala de aula - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The present study aims to present analysis of the categories, in which were collected in a conversation with the teacher of Portuguese Language early years of elementary school. The analyses presented, have the culmination of showing how still language teaching in schools still present difficulties to students in learning this discipline. According to the teacher, the difficulties exist because many teachers do not innovate their methodologies and there is no didactic sequence in the classes taught by them. Based on the teacher’s answers, we can take ideas that can help us to modernize the Portuguese language classes and make students have the pleasure to learn more easily and start to enjoy studying this discipline that for some students becomes a torment We need to be able to make it easier for these students to learn and earn a good living in their studies. To be a good student not only be able to read and write, but also to understand what you have written and read. Only then will they succeed in their careers, adding to education and forming good citizens. Reading, writing and speech are the main axes of this work in which it will be presented, based on research, ideas arise and changes take place. So to be good at what we do we have to make the different happen, because there is no middle ground, either you do it right or you don’t do it right.
Keywords: Trabalho; Diferenças; Mudanças; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE